Three Different Spectrophotometric Methods for Simultaneous Determination of Pyriproxyfen and Chlorothalonil Residues in Cucumber and Cabbage Samples - Shilan A. Omer; Nabil A. Fakhre (Journal of Spectroscopy)
In this study, three simple and accurate spectrophotometric methods for simultaneous determination of pyriproxyfen and chlorothalonil residues in cucumbers and cabbages grown in experimental greenhouse were studied. The first method was based on the zero-crossing technique measurement for first and second derivative spectrophotometry. The second method was based on the first derivative of the ratio spectra. However, the third method was based on mean centering of ratio spectra. These procedures lack any previous separation steps. The calibration curves for three spectrophotometric methods are linear in the concentration range of 1–30 μg·mL−1 and 0.5–7 μg·mL−1 for pyriproxyfen and chlorothalonil successively. The recoveries ranged from 82.12–97.40% for pyriproxyfen and 81.51–97.04% for chlorothalonil with relative standard deviations less than 4.95% and 5.45% in all instances for pyriproxyfen and chlorothalonil, respectively. The results obtained from the proposed methods were compared statistically by using one-way ANOVA, and the results revealed there were no significant differences between ratio spectra and mean centering methods with the zero-crossing technique. The proposed methods are successfully applied for the simultaneous estimation of the residue of both pesticides in cucumber and cabbage samples.